A strategic leadership framework for successful digital transformation: perspectives on leadership behaviors, styles & organisation culture - Ramalingam, Kasturi (2021)
The purpose of this study is to explore the experiences and perspectives of senior leaders who have led successful digital transformation in Malaysia to develop an in-depth understanding of key leadership behaviors, style(s) and organisation culture required to lead successful digital transformation. The main objective of this research is to a) identify the key leadership behaviors that influence successful digital transformation b) explore the key leadership style(s) that influence successful digital transformation c) examine the organisation culture that influence successful digital transformation d) investigate how leadership behaviors, style(s) and organisation culture influence successful digital transformation. The main research questions that this study aims to address is: a) what are the key leadership behaviors that influence successful digital transformation? b) what are the key leadership style(s) that influence successful digital transformation? c) what are the organisation culture that influence successful digital transformation? d) how these leadership behaviors, style(s) and organisation culture influence successful digital transformation? A qualitative research method is chosen to collect the data. Interviews was conducted with C-suite executives and head of business units from multiple industries using open-ended question to address the main research questions. The specific data collection and analysis methods used was thematic analysis using inductive research approach that allowed for in-depth exploration of behaviors, style(s) and culture involved in leading successful digital transformation. The findings showed 14 interrelated key components to lead successful digital transformation in Malaysia. A framework that depicts the 14 interrelated components organised into three dimensions: leadership behavior, style(s) and organisation culture that are important to lead successful digital transformation in Malaysia was developed that can benefit a) future leaders of organisations who are already successful in digital transformation b) leaders who are currently taking initiatives to transform their organisation or are considering starting a digital transformation journey c) small and medium sized enterprises, internal and third party change agents who are working with all level leaders in an organisation.